Development and Validation of a Bioanalytical UHPLC-MS/MS Method Applied to Murine Liver Tissue for the Determination of Indocyanine Green Loaded in H-Ferritin Nanoparticles - Sottani, Cristina; Grignani, Elena; Cottica, Danilo; Mazzucchelli, Serena; Sevieri, Marta; Chesi, Arianna; Corsi, Fabio; Galfrè, Sarah; Robustelli della Cuna, Francesco Saverio; Calleri, Enrica (Frontiers in Chemistry, 2022)
Indocyanine Green (ICG) ICG is one of the most commonly used fluorophores in near-infrared fluorescence-guided techniques. However, the molecule is prone to form aggregates in saline solution with a limited photostability and a moderate fluorescence yield. ICG was thus formulated using protein-based nanoparticles of H-ferritin (HFn) in order to generate a new nanostructure, HFn-ICG. In this study, a high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) system was employed to develop and validate the quantitative analysis of ICG in liver tissue samples from HFn-ICG treated mice. To precipitate H-Ferritin cold acetone in acidic solution at pH 5.0 was used. The processed liver samples were injected into the UHPLC-MS/MS system for analysis using the positive electrospray ionization mode. Chromatographic separation was achieved on an ACQUITY UPLC® HSS T3 Column (1.8 m, 2.1 x 100 mm) with 0.1% formic acid and acetonitrile as the mobile phase with gradient elution. The selected reaction monitoring transitions of m/z 753 → m/z 330 and m/z 827 → m/z 330 were applied for ICG and IR-820 (the internal standard, IS), respectively. The method was selective and linear over a concentration range of 50–1500 ng/mL. The method was validated for sensitivity, accuracy, precision, extraction recovery, matrix effect, and stability in liver tissue homogenates. ICG extraction recoveries ranged between 85% and 107%. The intra-and inter-day precisions were less than 6.28%. The method was applied to a bio-distribution study to compare the amount of ICG levels from mice treated with HFn-ICG and free ICG.